DINAMIKA KEBIJAKAN PENGGUNAAN KAWASAN HUTAN: SEBUAH ANALISA ISI PERUBAHAN KEBIJAKAN PENGGUNAAN KAWASAN HUTAN - Kushartati Budiningsih; Sulistya Ekawati; Handoyo Handoyo (Jurnal Analisis Kebijakan Kehutanan, 2016)
The designation of forest area for the purposes of non-forestry sector has to be done through the mechanism of exchange and lease forest areas. The policies regarding these mechanism changed dinamically. This study examined changes in the policy of the mechanism, factors driving these changes and their implications. The results showed that the changes of forest areas used by expanding to the commercial interests, the criteria exchanged forest areas, lease license validity period, the criteria of replacement land / land compensation, the ratio of replacement land, and monitoring-evaluating activities. The factors driving these changes include economic factors, political and social. The effective monitoring and evaluation activities become one of the keys to overcoming the problem of policy implementation in the exchange or lease of forest areas.